Fast and non-destructive Raman spectroscopic determination of multi-walled carbon nanotube (MWCNT) contents in MWCNT/polydimethylsiloxane composites. Issue 18 (16th August 2018) - Ryoo, Donghyun; Kim, Jong Yun; Duy, Pham Khac; Cho, Sang Hoon; Chung, Hoeil; Yoon, Tae Hyun
Abstract : A versatile Raman spectroscopic method to determine the contents of carbon nanotubes (CNTs) in CNT/polydimethylsiloxane (PDMS) composites is demonstrated, and important issues directly related to the accuracy of the measurement were investigated. Abstract : A versatile Raman spectroscopic method to determine the contents of carbon nanotubes (CNTs) in CNT/polydimethylsiloxane (PDMS) composites is demonstrated, and important issues directly related to the accuracy of the measurement have been investigated. Initially, Raman microscopic mappings over an area of 6.0 × 6.0 mm 2 were carried out on CNT/PDMS composites, which revealed the existence of the partial localization of CNTs on a microscopic scale. Therefore, a laser illumination scheme covering a large sample area of 28.3 mm 2 was employed to acquire a sample spectrum representative of the whole CNT concentration. The peak area ratio between the CNT and PDMS peaks clearly varied with the CNT concentration, whereas the reproducibility of measurements was degraded for the composites containing more than 3.0 wt% CNTs because of the decreased Raman sampling volume arising from the absorption of laser radiation by the CNTs. The laser penetration depth was semi-quantitatively investigated by observing the spectra of thin-sliced samples collected by positioning a Teflon disk behind the sample, and Monte Carlo simulations were employed to examine the internal photon propagation as well as explain the experimental observation. In summary, the fundamental issues affecting the Raman measurement of the CNT containing polymer matrix have been clearly addressed, and the finding here will be a beneficial basis for successful Raman spectroscopic analysis of different CNT-containing composites.